Profil Kompetensi Pelatih Sepakbola Usia Dini - Rohman, Ujang (Journal Sport Area, 2018)
This study aimed to find out and formulate the profile of coaches for young soccer players that can be seen from competencies requirements. Based on its purpose, this research was descriptive study with a mixed method approach. Objective of this study were the coaches of young soccer players in SSB of Surabaya city. This research design was sequential exploratory design and the data collection techniquewas done by using survey techniques through questionnaire, observation, and interview. Based onthe quantitative data analysis, it found that coaches profile of young soccer playerswere X1= 0.59 (59%) as must has charisma, X3=0.55 (55%) as has motivation, X4= 0.53 (53%)as comprehend basic techniques of soccer playing and X2= 0.50 (50%) as has playing skill. Qualitative data described that the coach profile of young soccer players must have charisma, motivation, understanding of technique, and playing skill of soccer. Based on that analysis result, it can be concluded that the competencesprofile that must be acquired by the coaches of young soccer playersconceptually are attitude, knowledge and skill competence.